PERLINDUNGAN BAGI PENCARI SUAKA, IMPLIKASI DAN TANTANGAN BAGI PENGUNGSI DAN NEGARA TUAN RUMAH - Habibah Zulaiha; Ahmad Soleh; Zainal Efendi Hasibuan; Taupiq (Yayasan Baitul Hikmah al-Zain, 2025)
This article will describe the increase in global migration triggered by various factors such as armed conflict, political instability, and natural disasters. This has led to a rise in the number of refugees, asylum seekers, and illegal migrants who require appropriate handling. The research method used is library research with a qualitative descriptive approach, involving the analysis of secondary data from various literature, including international policies and case studies from countries that are migration destinations. The research findings indicate that there is significant legal uncertainty in dealing with these groups, which impacts the increase in economic and social burdens in host countries. Additionally, political and social tensions often arise due to inconsistent immigration policies.